2021
DOI: 10.1186/s12909-021-02753-1
|View full text |Cite
|
Sign up to set email alerts
|

Simulation-based training following a theoretical lecture enhances the performance of medical students in the interpretation and short-term retention of 20 cross-sectional transesophageal echocardiographic views: a prospective, randomized, controlled trial

Abstract: Background Both simulation-based training and video-based training serve as educational adjuncts for learning TEE among medical students. In the present study, we hypothesized that simulation-based training would better enhance the performance of medical students in the interpretation of 20 cross-sectional views compared to video-based training. Methods A total of 120 4th-year undergraduate medical students were enrolled in the present study. The s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 27 publications
0
12
0
Order By: Relevance
“…Furthermore, a recent study claimed cesarean section practice using mannequin simulation demonstrated important knowledge improvement, particularly in suturing ability [ 29 ]. Simulation of clinical practice improved performance more than a single video tutorial in medical students [ 19 ]. This method allowed residents to gain experiment chances repeatedly along with a minimum stress environment [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Furthermore, a recent study claimed cesarean section practice using mannequin simulation demonstrated important knowledge improvement, particularly in suturing ability [ 29 ]. Simulation of clinical practice improved performance more than a single video tutorial in medical students [ 19 ]. This method allowed residents to gain experiment chances repeatedly along with a minimum stress environment [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…The other learning methods were required to achieve clinical skill competencies. Mannequin simulation and video tutorials could be alternative approaches in educational institution [ 19 ]. The limited number of mannequins causes simulations using mannequins to be carried out by students at the same location and time [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is due to the growing knowledge of the community as customers, as evidenced by changes in increasingly critical attitudes, increased competition, higher demands for the workplace, and rapid technological changes. This change increases competition among universities (Zhao et al, 2021). A university should have various facilities to compare performance in providing quality service.…”
Section: Introductionmentioning
confidence: 99%